3-Cyano thiophene-based π-conjugated mesogens: XRD and 13C NMR investigations. Issue 5 (9th April 2019) - Pratap, G.; Malkar, Deepshika; Varathan, E.; Lobo, Nitin P.; Roy, Arun; Narasimhaswamy, T.
ABSTRACT: 3-Cyano thiophene-centred π-conjugated mesogens with alkoxy phenyl/biphenyl rings are synthesised by palladium acetate-catalysed direct arylation to investigate the mesophase properties and the molecular order. The synthesised mesogens mostly exhibit smectic A mesophase as confirmed by X-ray diffraction studies. Further, due to the manifestation of π-conjugated core, the mesogens exhibit photo luminescence in solution with emission maxima in the range 425–460 nm. Density functional theory and time-dependent density functional theory calculations of a representative mesogen indicate possible intramolecular charge transfer transition between the biphenyl to 3-cyanothiophene units. Despite structural simplicity, the observation of smectic A phase is attributed to location of strong dipole moment component perpendicular to the long axis of the molecules due to the presence of polar cyano group at 3-position of central thiophene ring. The 13 C NMR studies are performed in mesophase and using the 13 C– 1 H dipolar couplings determined from 2D separated local field experiment; the order parameters of central thiophene ring and side arm phenyl rings are calculated. Moreover, the order parameter ratios of thiophene and side arm phenyl rings indicate the bent–core nature of the mesogen. Graphical Abstract: